Kajian Potensi Limbah Pertanian Sebagai Pakan Ternak Ruminansia di Kabupaten Aceh Besar - Samadi Samadi; Yunasri Usman; Mira Delima (Jurnal Agripet, 2010)
Evaluation of the potency of agricultural by product as ruminant animal feed in aceh besar regencyABSTRACT. A research to evaluate the potency of agricultural by product as animal feed was conducted in Aceh Besar Regency from June to December 2009. The purpose of this research is to evaluate the availability of local feed from agricultural by product including its production and quality, to calculate animal capacity of ruminant animals by using animal unit (AU) based the production and quality of agricultural by product.This research was carried out by survey method. Data consist of primary and secondary data to calculate the production and quality of agricultural by products in Aceh Besar Regency. The production of agricultural by products was calculated based on dry matter, crude protein and total digestible nutrient. Animal capacity which is calculated based on agricultural by products with the following measurement ; 1 animal unit consumes dry matter with the average of 6,25 kg/day (2.282,25 kg/year), crude protein with average of 0,06 kg/day (240,9 kg/year) and total digestible nutrient with the average of 4,3 kg/day (1.569,5 kg/year).Based on the calculation was found that total of dray matter, crude protein and total digestible nutrient from agricultural by product in Aceh Besar regency was 197.510 ton, 9443,8 ton and 89.167,7 ton respectively. The capacity of ruminant animals fed from agricultural by product in Aceh Besar regency was 87.061 AU, 39.202 AU, and 57.125 AU for dry matter, crude protein and total digestible nutrient respectively. It can be concluded that Aceh Besar regency has a big potency to develop animal production by using agricultural by products. Therefore, agricultural by products in Aceh Besar regency should be used optimally.